PENGEMBANGAN LEMBAR KERJA SISWA (LKS) FISIKA BERBASIS PENEMUAN TERBIMBING BERBANTUAN SIMULASI KOMPUTER - Nikmatul Khoiriyah; Agus Suyatna; I Dewa Putu Nyeneng (Jurnal Pembelajaran Fisika, 2013)
The Purpose of development is to make worksheet based guided discovery, knowing learning outcomes and responses’s students on the worksheet. The Development procedures that used are: 1) identification of needs, 2) the development design formulation and tool for measuring success, 3) product development, 4) product trials, 5) revision and product ready. The research’s result is worksheet shaped practical instructions for PhET simulation’s program of Ohm's law and Kirchoff's law 1 experiments. Worksheet effective because 84.2% students completed the test. The average of students’s learning outcomes is 87 with standard deviation of 11. Student performance is very good with a percentage of 93.02%. Attitude of students during learning process using worksheet is very positive with percentage of 82.83%. Based on test result got attractiveness score is 3,17 and easiness score is 3,05 so worksheets attractive and easy used by students.Tujuan pengembangan ini adalah membuat LKS berbasis penemuan terbimbing, mengetahui hasil belajar siswa dan tanggapan siswa terhadap LKS tersebut. Prosedur pengembangan yang digunakan antara lain: 1) identifikasi kebutuhan, 2) perumusan desain pengembangan dan alat ukur keberhasilan, 3) pengembangan produk, 4) uji coba produk, 5) revisi dan produk siap. Hasil penelitian berupa LKS berbentuk petunjuk praktikum sebagai panduan program simulasi PhET, percobaan hukum Ohm dan hukum 1 Kirchoff. LKS efektif karena 84,2 % siswa tuntas. Rata-rata hasil belajar adalah 87 dengan simpangan baku sebesar 11. Keterampilan siswa sangat baik dengan persentase sebesar 93,02 %. Sikap siswa selama pembelajaran menggunakan LKS sangat positif dengan persentase sebesar 82,83 %. Berdasarkan hasil uji diperoleh skor kemenarikan 3,17 dan skor kemudahan 3,05 sehingga LKS menarik dan mudah digunakan oleh siswa.Kata kunci: pengembangan, lembar kerja siswa, penemuan terbimbing